Hubungan Edukasi Disminore terhadap Peningkatan Pengetahuan pada Remaja Putri di SMK Pasundan - Ina Sugiharti; Ecih Winengsih; Meda Yuliani; Dyah Ayu Fitriani (Pusat riset dan Inovasi Nasional, 2026)
Menstrual pain (dysmenorrhea) is a common complaint among adolescent girls and often disrupts school activities. Limited understanding of its causes and appropriate self-care practices contributes to the persistence of symptoms. This study examined the effect of dysmenorrhea health education on improving knowledge among female students at SMK Pasundan Jatinangor. A method A pre-experimental one-group pretest–posttest design was used in this study. A total of 42 students participated and completed a dysmenorrhea knowledge questionnaire before and after a 60-minute educational session delivered through presentation media and group discussion. The results were analyzed descriptively to observe changes in knowledge levels. Resulted The intervention produced a notable improvement in students’ knowledge. The proportion of participants with good knowledge increased from 45.2% at pretest to 73.8% at posttest, while those in the low-knowledge category decreased substantially. Participants demonstrated clearer understanding of dysmenorrhea symptoms, contributing factors, and simple management strategies. Dysmenorrhea education effectively enhanced students’ knowledge at SMK Pasundan Jatinangor. Regular reproductive-health education programs in schools are recommended to support adolescents in managing menstrual discomfort independently and appropriately.